Обогащение лексикона студентов с использованием новых информационно-коммуникативных технологий (на примере сервисов WorldWall и LearningApps) - Dźwierzyńska, Ewa (Studia Rossica Posnaniensia, 2022)
The article is the result of a search for effective tools that can support the process of enriching the individual lexicon of students. The possibilities of involving students in this process through the use of selected ICT tools were indicated. It was pointed out that the use of various platforms and mobile applications in the development and control of lexical skills is conducive to individualization of teaching, and its inclusion in the learning process requires an analysis for usefulness in achieving expected learning outcomes. Online learning platforms such as WordWall and LearningApps, that allow for the design of interactive exercises facilitating the learning of foreign languages, and in particular the improving of foreign vocabulary, were analyzed. Their use in the course of independent learning enables the enrichment of vocabulary in accordance with the interests and individual communication needs of students. The inclusion of these tools in the didactic process may positively affect the motivation to learn, and their systematic use, both in the classroom and during individual work, it also allows the acceleration of the memorization of the vocabulary of a foreign language.